Reconstruction of Islamic-Based Marriage Law Politics: A Comparison between Legal Traditions in the Middle East and Southeast Asia - Abbas Sofwan Matlail Fajar; Karmawan; Nur Rohim Yunus (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose - This article aims to analyze the reconstruction of Islamic-based marriage law politics through a comparative approach between the legal traditions of the Middle East and Southeast Asia. The study examines how legal politics shapes the codification of family law and the extent to which reconstruction is needed to address the challenges of justice and modernity. Method - This study employs a normative-comparative method, drawing on a legal politics approach and comparative Islamic law. The data are drawn from primary legal materials (marriage laws, Islamic legal compilations, and family regulations in Muslim-majority countries) and secondary legal materials, including academic literature. The analysis is conducted through content analysis and comparison of legal systems. Findings - The findings indicate that legal politics plays a dominant role in shaping Islamic-based marriage regulations. The legal tradition in the Middle East tends to preserve classical fiqh with a high degree of conservatism. In contrast, Southeast Asia is more adaptive through codification and harmonization with national legal systems. A reconstruction of legal politics is necessary to integrate the principles of maqāṣid al-sharīʿah with the demands of universal justice. Research Implications - This study contributes to the development of Islamic legal politics theory and serves as a reference for policymakers in formulating marriage regulations that are responsive to social dynamics. Originality/Value - This study offers a new perspective on the reconstruction of Islamic-based marriage law politics through a cross-regional comparative analysis, a subject rarely examined in depth in contemporary Islamic legal literature.